NRF2 Activation Ameliorates Oxidative Stress and Improves Mitochondrial Function and Synaptic Plasticity, and in A53T α-Synuclein Hippocampal Neurons - Mikah S. Brandes; Jonathan A. Zweig; Anita Tang; Nora E. Gray (MDPI AG, 2021)
In Parkinson's disease (PD), brain oxidative stress and mitochondrial dysfunction contribute to neuronal loss as well as motor and cognitive deficits. The transcription factor NRF2 has emerged as a promising therapeutic target in PD because it sits at the intersection of antioxidant and mitochondrial pathways. Here, we investigate the effects of modulating NRF2 activity in neurons isolated from a A53T α-synuclein (A53TSyn) mouse model of synucleinopathy. Embryonic hippocampal neurons were isolated from A53TSyn mice and their wild type (WT) littermates. Neurons were treated with either the NRF2 activator dimethyl fumarate (DMF) or the NRF2 inhibitor ML385. Reactive oxygen species (ROS), dendritic arborization and dendritic spine density were quantified. Mitochondrial bioenergetics were also profiled in these neurons. A53TSyn neurons had increased ROS and reduced basal and maximal mitochondrial respiration relative to WT neurons. A53TSyn neurons also displayed decreased dendritic arborization and reduced spine density. Treatment with DMF reduced ROS levels and improved both mitochondrial function and arborization, while inhibition of NRF2 with ML385 exacerbated these endpoints. Modulation of NRF2 activity had a significant effect on mitochondrial function, oxidative stress, and synaptic plasticity in A53TSyn neurons. These data suggest that NRF2 may be a viable target for therapeutic interventions in PD.